Parathyroid Cysts : the Latin-American Experience (2016)
ABSTRACT: Background: Parathyroid cyst is an infrequent and unsuspected disease. There are more than 300 hundred cases reported in the world literature, a few of them are from Latin America. The experience of our centers and a review of the cases are presented. Methods: Case report of a series of patients with parathyroid cyst from our institutions according to the CARE guidelines (Case Reports). A search of Medline, Embase, BIREME (Biblioteca Regional de Medicina) LILACS (Literatura Latinoamericana y del Caribe en Ciencias de la Salud), Google Scholar and Scielo (Scientific Electronic Library on Line) databases and telephonic or email communications with other experts from Latin-America was performed. Results: Six patients with parathyroid cyst were found in our centers in Colombia. Most of them were managed with aspiration of the cyst. Two of them required surgery. Only one case was functional. Twelve reports from Latin America were found for a total of 18 cases in our region adding ours. Conclusions: Parathyroid cysts are uncommonly reported in Latin America. Most of them are diagnosed postoperatively. Suspicion for parathyroid cyst should be raised when a crystal clear fluid is aspirated from a cyst. The confirmation of the diagnosis may be easily done if parathyroid hormone (PTH) level is measured in the cyst fluid.